The future of vocational education and training in a changing world - Pilz, Matthias (VS Verlag fur Sozialwissenschaften, 2012)
Across the globe, vocational education and training is characterised by a number of over-arching trends, including the increasing use of technology, the growing importance of information and communications systems, and changes to national demographics. At the interface between the education and training system and the world of work, VET faces the challenge of tackling these changes, of making a constructive contribution to solving the problems posed by the transition from education to employment, and of ensuring that the next generation has the skills it - and the economy - needs. This volume comprises thirty individual contributions that together add up to a comprehensive overview of the current situation in vocational education and training, its strengths and weaknesses, and its prospects. VET experts from Canada, the USA, India, China, Japan and Korea, as well as from a number of European countries, focus on their national context and how it fits in to the bigger picture. The contributions combine theoretical discussions from various strands of VET research with evidence from country case studies and examples from current practice.